Evaluation of Forest Resources Conservation Laws In Nigeria - Abere , S. A.; Jasper, Ezenwaka (Mediterranean Journal of Social Sciences, 2011)
This paper sets out to explore the effectiveness of forest conservation laws in Nigeria.The forest has servedas a source of livelihood to people in Nigeria for many generations (Ezenwaka & Abere 2009). It is a sourceof income, employment, food, medicine, recreation and vital raw materials for many purposes includingconstruction. However, many factors are threatening the sustainability of this source of people’s survival(Ezenwaka 2008). Scientific approaches of conservation and or preservation has been proposed (e.g.government setting aside reservation areas through laws) but these are not yielding the anticipated results (ofconserving the bio-diversity) as illegal and unsustainable hunting and harvesting of the forest resources arestill observed (LENF 1998).